A Comparison of foreign and local garment brands' functional strategies - Villaflores, Anna Thea C.; Rayala, Maria Monica (Quezon City College of Home Economics, University of the Philippines Diliman, 2015)
ABSTRACT In this age of globalization, there is a growth of global media, increase in world travel, and expansion of a company's operations, which brings about an influx of foreign brands to the domestic market. For that reason, local and foreign garment brands are vying for Filipino consumers through their functional strategies. This descriptive research aimed to compare the functional strategies of local and foreign garment brands based on the perspective of selected young Filipino consumers. This was achieved by identifying the functional strategies of local and foreign garment brands, determining the effectiveness of functional strategies of local and foreign garment brands through consumer evaluation, and identifying the consumer preference based on the functional strategies of local garment brands versus foreign garment brands. The study conducted a survey on 54 purposively selected Filipino female consumers, aged 17-23 from upper to middle economic status, regarding the effectiveness of functional strategies of foreign and local garment brands. It was found that respondents prefer the pricing strategies of local garment brands whereas they prefer product variety and availability, publicity and advertising, electronic merchandising, discounts and markdowns, and store space and atmosphere of foreign garment brands. The result of this study may aid brands in discerning their competitive advantage, determining their strength and weaknesses, and identifying which functional strategies to retain or improve.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Clothing and dress -- Philippines